SEXUALIDADE E FORMAÇÃO DE PROFESSORES: ALGUMAS CONSIDERAÇÕES - Ademir Henrique Manfré; Camila Medeiros de Araujo; Daniele Cristina Nogueira Gonçalo (Universidade do Oeste Paulista, 2016)
This article is a result of an empirical research into the main theme of sexuality, toward the infantile sexuality in school Proposes to present the importance of the approach this theme along with the design and laying of professor on the topic discussed in the classroom .We carry out the implementation of structured questionnaires containing ten (10) open questions focused on training, opinion and attitudes of teachers who teach in the first cycle of basic education in public schools. By the due registration of research with the protocol number 2768, approved by the Research Ethics Committee (CEP), the application of those questionnaires.We present, in this article, the partial results of our investigation, as well as the categories arising from the analysis of the first and second issue of our questionnaire, along with a brief discussion.